Interactive Client-Side Network Simulation with Dynamic Bandwidth Management and Real-Time 3D Visualization - Lukman, Lukman; Sri Nugraha, Bhanu (Jurnal PROCESSOR, 2025)
Effective network management in dynamic environments necessitates robust tools for real-time analysis and visualization. This paper presents a client-side network simulation designed to model and visualize complex network behaviors, including dynamic bandwidth allocation, traffic spillover across multiple Internet Service Providers (ISPs), and system-wide congestion throttling. Leveraging Three.js, the system procedurally generates a 25-node network topology and simulates fluctuating traffic demands using a stochastic model. A central router implements a hierarchical spillover logic for external traffic and a proportional throttling algorithm to cap total bandwidth, ensuring network stability under peak loads. Real-time data visualization is achieved through animated data packets, color-coded node states, and an overlaid 2D time-series graph. Validation confirms the system's functional validity, demonstrating its potential as an educational tool and a proof-of-concept for sophisticated digital twins for network operations.